1969
DOI: 10.1103/physrev.179.494
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Effects on the Conductivity of a Superconductor above Its Transition Temperature

Abstract: We study the conductivity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…In the limit g → 0 the electric-field-dependent conductivity can be written in a simple form 15) and thus the nonlinear electric-field correction to the conductivity reads…”
Section: Paraconductivity In a Layered Metalmentioning
confidence: 99%
“…In the limit g → 0 the electric-field-dependent conductivity can be written in a simple form 15) and thus the nonlinear electric-field correction to the conductivity reads…”
Section: Paraconductivity In a Layered Metalmentioning
confidence: 99%
“…As it can be noticed, we define the relaxation rate Γ −1 0 as depending on the actual temperature T , while in many other works, 3,19,23 it is defined as a function of the mean-field critical temperature, T 0 . Of course the difference is negligible near the transition point, but one must recall that in the derivation of the GL equations from the BCS theory, 21,24,25 the temperature is usually approximated with the critical one, while the reduced temperature ln (T /T 0 ) is approximated with (T − T 0 ) /T 0 .…”
Section: Tdgl Equation For Arbitrary Electric Fieldmentioning
confidence: 99%
“…2 However, it was shown that the fluctuation conductivity may be calculated in the linearresponse approximation only for sufficiently weak fields, when they do not perturb the fluctuation spectrum. 3 Reasonably high values of the electric field E can accelerate the fluctuating paired carriers to the depairing current, and thus, suppress the lifetime of the fluctuations, leading to deviation from Ohm's law. In connection with the low-temperature superconductors, the nonlinearity has been studied theoretically for the isotropic case 4,5 and also proven experimentally on thin aluminum films.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism can be summarized by saying that reasonably high values of the electric field, comparable to the so-called critical field E c (T ), can accelerate the fluctuating paired carriers to the depairing current, and thus, suppress the lifetime of the fluctuations, leading to deviation from Ohm's law. The non-Ohmic behavior of the fluctuation paraconductivity in sufficiently strong electric fields was studied about three decades ago in connection with the low temperature superconductors both theoretically, for the isotropic case [6,7,8], and experimentally, on thin aluminum films [9,10], with a good agreement between experiment and theory. The issue of the non-Ohmic fluctuation conductivity for a layered superconductor, a situation very much resembling the crystal structure in the HTS, has been addressed theoretically a decade ago starting from a microscopic approach [11], and more recently, in the frame of the time-dependent Ginzburg-Landau (TDGL) theory, in the Gaussian approximation [12], and in the self-consistent Hartree approach [13].…”
Section: Introductionmentioning
confidence: 94%